2013
DOI: 10.1002/lite.201300289
|View full text |Cite
|
Sign up to set email alerts
|

Hydroformylation of vegetable oils and the potential use of hydroformylated fatty acids

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 7 publications
0
13
0
2
Order By: Relevance
“…In the early 2000s, awareness of the depletion of fossil fuels and the subsequent increase in the oil barrel price revitalized this research sector in the wake of the 12 principles of green chemistry set forth by Anastas and Warner in 1998. Even though some recent reviews summarized works carried out in the 70s , the increasing number of recent articles dealing with the catalytic hydroformylation of fatty compounds reflects the growing interest of the scientific community in this field. Currently, the shale gas revolution poses again the problem of the profitability of bio‐based products with respect to fossil feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 2000s, awareness of the depletion of fossil fuels and the subsequent increase in the oil barrel price revitalized this research sector in the wake of the 12 principles of green chemistry set forth by Anastas and Warner in 1998. Even though some recent reviews summarized works carried out in the 70s , the increasing number of recent articles dealing with the catalytic hydroformylation of fatty compounds reflects the growing interest of the scientific community in this field. Currently, the shale gas revolution poses again the problem of the profitability of bio‐based products with respect to fossil feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalization of vegetable oils using various chemical methods such as epoxidation, alkylation, metathesis, hydroxylation, rearrangements, etc., has received ample attention because of the resulting product applications in the chemical industry [2,23]. Recently, it has been shown that hydroformylation can be used to functionalize fatty acid derivatives at the site of unsaturation, and the resulting products are useful as plasticizers and lubricants [24,25]. Similarly, the derivatives of certain functional groups such as epoxidized oils and their derivatives show promise as plasticizers as they increase the polarity and improve the compatibility with polyvinyl chloride (PVC).…”
Section: Resultsmentioning
confidence: 99%
“…Unsaturated double bonds along the fatty acids are oxidized first to produce aldehyde groups followed by a reduction to hydroxyl groups [71]. In hydroformylation, aldehyde groups are generated first through the reaction of double bonds with hydrogen and carbon monoxide, then are converted to hydroxyl group [72]. Another possible route to yield hydroxyl group along the fatty chain is photochemical oxidation, during which fatty acids are oxidized with sunlight source in a rich oxygen environment once exposed to high-pressure sodium-vapor lamp and tetraphenyl porphyrin as a sensitizer to produce allylic hydroperoxide [71].…”
Section: Pu Foammentioning
confidence: 99%